Simulation and economic analysis of an AGV system as a mean of transport of warehouse waste in an automotive OEM - Silva, Tomé (2016)
Companies with high quality production systems like the automotive industry OEM's (Original Equipment Manufacturer), need to control the containers in which the raw materials are delivered onto the production lines to make sure quality standards are not breached. They commonly have to change the containers from their suppliers to special clean vessels. Hence a new flow of residues is created by this repacking process, the problem arises with the need to minimize the impact that this flow has on the milk runs that supply the lines with raw materials and maintaining the cost of its operation as low as possible. Different AGV (Automated Guided Vehicles) system configurations were tested based on their financial and functionality feasibility to see if the use of AGVs is viable to perform this kind of activities. SIMIO simulation tool was used to assess the performance of each AGV configuration on the metrics of buffer size, total travelled distances, resource utilization and effect on the output of the plant for four different production levels (units/shift). A configuration was clearly better, for the highest production level scenario: it freed 12 m2 of buffer area; it reduced operators travelled distances by 88%; it was suitable for 120% of the current production levels; had a payback time of less than 2 years and a net present value of 232K€.